Impact of pharmacy collaborating services in an outpatient clinic on improving adverse drug reactions in outpatient cancer chemotherapy. (October 2019) - Suzuki, Hidetaka; Suzuki, Shinya; Kamata, Hayato; Sugama, Yuka; Demachi, Ken; Ikegawa, Kiwako; Igarashi, Takashi; Yamaguchi, Masakazu
Background: Collaboration between pharmacists, doctors, and nurses in outpatient treatment is beneficial; however, such services are limited in Japan due to the lack of a healthcare reimbursement fee for outpatient pharmacy services at outpatient clinic. Objective: We evaluated the impact of a service in which clinical pharmacists collaborated with an oncologist at an outpatient clinic in the treatment of adverse drug reactions in outpatient cancer chemotherapy. Methods: We performed a retrospective cohort study using patients' medical records and treatment diaries. Subjects were patients who received outpatient chemotherapy via a clinical pharmacist collaboration service provided by six outpatient pharmacists and an oncologist at an outpatient clinic between June and August 2016. Results: During the study period, the total number of outpatient services was 2508, with 2055 (81%) related to chemotherapy. The six outpatient pharmacists provided interventions to 498 of the 2055 cases (24%). Of the 498 interventions, 103 (20%), in addition to oncologist's prescription, were suggested treatments for adverse drug reactions due to cancer chemotherapy. Oncologists approved a total of 82 prescription suggestions from pharmacists (79%) to 63 patients. Fifty-seven percent ( n = 47) of the adverse drug reactions were improved following the pharmacists' suggested prescriptions. Conclusions: This is the first study to clarify the benefits of outpatient pharmacy services in which pharmacists collaborate with oncologists at an outpatient clinic for the management of adverse drug reactions in cancer patients in Japan.